ESTIMASI POTENSI BIOGAS DARI PALM OIL MILL EFFLUENT (POME) PABRIK KELAPA SAWIT DI PROVINSI JAMBI - Guntar Marolop S; Hadrah Hadrah (Jurnal Civronlit Unbari, 2018)
The increasing of palm oil mills as a result of an increase in public interest of land exploitation to produce  palm oil can cause high environmental pollution if the waste oil generated were not managed properly. Palm Oil Mill Effluent (POME) is the wastewater generated by palm oil extraction process. On the other hand, POME is a renewable energy source. To address the need for electrical energy increases, the monitoring of POME is an effort that needs to be studied because POME is no longer a pollutant to the environment but a helpful resource.This study uses field data collection in the form of POME volume and treatment plant process management to determine the COD levels so that the estimation of total biogas can be done. Based on the calculation of the energy potential of POME in Jambi province with  processing capacity of the entire Province amounted to 1,230 tons FFB / hour, 20 hours operating time / day and COD content of 50,000 mg / L, the amount of energy can be obtained is 737.712 MWh / day or 269.26 GWh / Year.Keywords: POME, biogas, energy